Microwave induced synthesis of graft copolymer of binary vinyl monomer mixtures onto delignified Grewia optiva fiber: application in dye removal - Gupta, Vinod Kumar; Pathania, Deepak; Priya, Bhanu; Singha, Amar Singh; Sharma, Gaurav (Frontiers in Chemistry, 2014)
Grafting method, through microwave radiation technique is very effective in terms of time consumption, cost effectiveness and environmental friendliness. Via this method, delignified Grewia optiva identified as a waste biomass, was graft copolymerized with methylmethacrylate (MMA) as an principal monomer in a binary mixture of ethyl methacrylate (EMA) and ethyl acrylate (EA) under microwave irradiation (MWR) using ascorbic acid/H2O2 as an initiator system. The concentration of the comonomer was optimized to maximize the graft yield with respect to the primary monomer. Maximum graft yield (86.32%) was found for dGo-poly(MMA-co-EA) binary mixture as compared to other synthesized copolymer. The experimental results inferred that the optimal concentrations for the comonomers to the optimized primary monomer was observed to be 3.19 mol/L×10-1 for EMA and 2.76 mol/L×10-1 for EA. Delignified and graft copolymerized fibre were subjected to evaluation of physicochemical properties such as swelling behaviour and chemical resistance. The synthesized graft copolymers were characterized with Fourier transform infrared spectroscopy (FTIR), scanning electron microscopy (SEM), thermogravimetric analysis (TGA) and X-ray diffraction techniques. Thermal stability of dGo-poly(MMA-co-EA) was found to be more as compared to the delignified Grewia optiva fibre and other graft copolymers. Although the grafting technique was found to decrease percentage crystallinity and crystallinity index among the graft copolymers but there was significant increase in their acid/base and thermal resistance properties. The grafted samples have been explored for the adsorption of hazardous methylene dye from aqueous system.